QT dispersion and P wave dispersion in patients with fibromyalgia - Yolbas, Servet; Yildirim, Ahmet; Duzenci, Deccane; Karakaya, Bulent; Dagli, Mustafa Necati; Koca, Suleyman Serdar (Aves, 2016)
Objective: Fibromyalgia (FM) is a chronic disease characterized by widespread pain. Somatic complaints associated with the cardiovascular system, such as chest pain and palpitations, are frequently seen in FM patients. P and QT dispersions are simple and inexpensive measurements reflecting the regional heterogeneity of atrial and ventricular repolarization, respectively. QT dispersion can cause serious ventricular arrhythmias. The aim of the present study was to evaluate QT dispersion and P wave dispersion in patients with FM. Material and Methods: The study involved 48 FM patients who fulfilled the established criteria and 32 healthy controls (HC). A standard 12-lead electrocardiogram was performed on all participants. QT dispersion was defined as the difference between the longest and the shortest QT intervals. Similarly, the differences between the shortest and longest P waves were defined as P wave dispersion. Results: The QT dispersion and corrected QT dispersion were shorter in the FM group compared with the HC group (p<0.001 for both). In terms of the P wave dispersion value, there was no significant difference between the FM and HC groups (p=0.088). Conclusion: Longer QT and P wave dispersions are not problems in patients with FM. Therefore, it may be concluded that fibromyalgia does not include an increased risk of atrial and/or ventricular arrhythmias.
Keywords: Fibromyalgia syndrome; QT dispersion; P wave dispersion